REALISME DAN ABSENNYA KEPEMIMPINAN GLOBAL: SITUASI KERJA SAMA INTERNASIONAL PADA WABAH VIRUS EBOLA DAN CORONA - Mergera Akbar Sinergi Putra Agung; Muhammad Faizal Alfian (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2022)
An outbreak of a disease or plague is a phenomenon in which a dangerous viral genome spreads and infects various individuals both domestically and internationally. At a more infectious stage, the spread of this disease can be classified into two categories; namely epidemic and pandemic. In early 2014 the Ebola virus originating from Africa spread in various regions in Africa and internationally, eventually causing the Ebola virus epidemic. Then in early 2020 the Corona virus or COVID-19 originating from Tiongkok spread to various regions in Tiongkok and internationally until finally causing the Corona virus pandemic. With this event, the international community should be able to work together to handle so that the spread of these two viruses can be reduced and finally controlled. However, when the spread of the Ebola and Corona viruses occurred, the international cooperation that took place seemed not optimal and was unable to handle the events that occurred. This study will analyze this by using the question “Why is international cooperation in dealing with outbreaks of infectious viruses such as Ebola and Corona difficult to do?”. The purpose of this study is to determine the factors that make international cooperation difficult to carry out despite the outbreak of dangerous viruses such as Ebola and Corona. This study uses an explanative qualitative research type. The main argument of this research is that the condition of the world without global leadership and the anarchic culture of international relations has resulted in non-optimal international cooperation in dealing with the Ebola and Corona virus outbreaks.